2022
DOI: 10.1103/physrevb.106.035102
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear nonreciprocal photocurrents under phonon dressing

Abstract: Nonlinear optical (NLO) effects have attracted great interest recently. However, by far the computational studies on NLO use the independent particle approximation and ignore manybody effects. Here we develop a generic Green's function framework to calculate the NLO response functions, which can incorporate various many-body interactions. We focus on the electron-phonon coupling and reveal that phonon dressing can make significant impacts on nonlinear photocurrent, such as the bulk photovoltaic (BPV) and bulk … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…These quantities, or equivalently the corresponding third-rank tensors σ a ; bc (ω) as a function of a single frequency, admit expressions in terms of the quasiparticle properties that are amenable to numerical evaluation via quantum mechanical methods. Specifically, these microscopic expressions can be obtained by diagrammatic approaches for the ballistic current; and by solving the density matrix perturbatively, employing Wilson loops or again by diagrammatic techniques for the injection and shift currents. However, only the latter one is truly intrinsic to the single-particle system, in the sense that it can be computed exclusively from the band structure and electronic eigenfunctions without further modeling.…”
Section: Introductionmentioning
confidence: 99%
“…These quantities, or equivalently the corresponding third-rank tensors σ a ; bc (ω) as a function of a single frequency, admit expressions in terms of the quasiparticle properties that are amenable to numerical evaluation via quantum mechanical methods. Specifically, these microscopic expressions can be obtained by diagrammatic approaches for the ballistic current; and by solving the density matrix perturbatively, employing Wilson loops or again by diagrammatic techniques for the injection and shift currents. However, only the latter one is truly intrinsic to the single-particle system, in the sense that it can be computed exclusively from the band structure and electronic eigenfunctions without further modeling.…”
Section: Introductionmentioning
confidence: 99%
“…In principle, the relaxation time τ might depend on k-points, band indices, and frequencies of light, because of impurity scattering, electron–phonons couplings, many-body interactions, etc. However, several previous studies have showed that it is still reasonable to consider an average and constant relaxation time approximation in the calculations of BPVEs. , Hence, in this study we adopt the constant relaxation time approximation and take the default value ℏ /τ = 1 meV; i.e., τ ≈ 0.6 ps. This setting is rather conservative since the MnPSe 3 is supposed to be a clean crystal due to its excellent chemical stabilities.…”
mentioning
confidence: 99%
“…However, several previous studies have showed that it is still reasonable to consider an average and constant relaxation time approximation in the calculations of BPVEs. [39][40] Hence, in this study we adopt the constant relaxation time approximation and take the default value ℏ/𝜏 = 1 𝑚𝑒𝑉, i.e., τ≈0.6 ps by default. This setting is rather conservative since the MnPSe3 is supposed to be a clean crystal due to its excellent chemical stabilities.…”
mentioning
confidence: 99%